Taurine and BAER Maturation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
A blinded randomized trial of taurine supplementation of preterm infants was conducted at the Department of Pediatrics, University of Texas Southwestern Medical Center, Dallas, and Ross Laboratories, Columbus, Ohio.